Effects of CO2 and liquid digestate concentrations on the growth performance and biomass composition of Tetradesmus obliquus and Chlorella vulgaris microalgal strains - Sánchez-Quintero, Ángela; Parsy, Aurélien; Adrien, Amandine; Spitzer, Lea; Jiménez-Lamana, Javier; Fernandes, Susana C. M.; Beigbeder, Jean-Baptiste (Frontiers in Bioengineering and Biotechnology, 2025)
This study evaluated the growth performance of Tetradesmus obliquus and Chlorella vulgaris microalgae cultivated in diluted liquid digestate supplemented with CO2, comparing their efficiency to a conventional synthetic media. The presence of an initial ammonium concentration of 125 mg N- NH4 + .L -1 combined with continuous injection of 1% v/v CO2 enhanced the optimal growth responses and bioremediation potential for both strains in 200 mL cultures. In 6 L flat panel reactors, T. obliquus exhibited superior biomass production, achieving a final biomass concentration of 1.29 ± 0.06 g.L -1 , while C. vulgaris reached only 0.36 ± 0.02 g.L -1 . Both strains effectively contributed to the bioremediation of the digestate-based culture media, with up to 100% of N-NH4 + , 50% of (chemical oxygen demand) COD and 55% of P-PO4 3-removals. The high nitrogen levels in the digestate-based medium resulted in significantly increased protein content, with 46.21 ± 3.98% dry weight (DW) for T. obliquus and 44.17 ± 2.24% DW for C. vulgaris as compared to the microalgae cultivated in commercial media. Additionally, the metal content of the microalgal biomass was analyzed to assess its potential use as biostimulants in compliance with European regulations. While chromium concentrations slightly exceeded regulatory thresholds in both strains, the levels of other metals remained within permissible limits.